Verapamil Alleviates Myocardial Ischemia/Reperfusion Injury by Attenuating Oxidative Stress via Activation of SIRT1 - Bao, Mi; Huang, Weiyi; Zhao, Yang; Fang, Xinzhe; Zhang, Yanmei; Gao, Fenfei; Huang, Danmei; Wang, Bin; Shi, Ganggang (Frontiers in Pharmacology, 2022)
Myocardial ischemia/reperfusion (I/R) injury is a potential complication of ischemic heart disease after recanalization. One of the primary reasons for I/R injury is the excessive accumulation of reactive oxygen species (ROS) in cardiomyocytes. Verapamil, a classic calcium channel blocker, has the potential to mitigate I/R-evoked oxidative stress. However, the underlying mechanisms have not been fully elucidated. SIRT1 is an essential regulator of I/R and offers resistance to oxidative stress arising from I/R. It is still inconclusive if verapamil can reduce myocardial I/R-triggered oxidative damage through modulating SIRT1 antioxidant signaling. To verify our hypothesis, the H9c2 cardiomyocytes and the mice were treated with verapamil and then exposed to hypoxia/reoxygenation (H/R) or I/R in the presence or absence of the SIRT1 inhibitor EX527. As expected, verapamil stimulated SIRT1 antioxidant signaling evidenced by upregulation of SIRT1, FoxO1, SOD2 expressions and downregulation of Ac-FoxO1 expression in vitro and in vivo. In addition, verapamil remarkably suppressed H/R and I/R-induced oxidative stress proven by declined ROS level and MDA content. The cardioprotective actions of verapamil via SIRT1 were further confirmed in the experiments with the presence of the specific SIRT1 inhibitor EX527. We demonstrated that verapamil alleviated myocardial I/R-evoked oxidative stress partially via activation of SIRT1 antioxidant signaling. Subsequently, verapamil protected against cardiac dysfunction and myocardial infarction accompanied by oxidative stress.